2011
DOI: 10.1002/pssa.201000734
|View full text |Cite
|
Sign up to set email alerts
|

Domain structure, magnetic properties, and giant magnetoimpedance of FeNi/Ti‐based multilayers

Abstract: Magnetic multilayers consisting of magnetic FeNi and non‐magnetic Ti layers were prepared by rf‐sputtering. Magnetic measurements and magnetic domain structure observations were used for characterization of the samples. The magnetoimpedance performance of FeNi/Ti‐based multilayers is evaluated in terms of the magnitude of the effect and its sensitivity with respect to applied magnetic field. The results show that the trilayer with Ti layer of 6 nm (sample A), deposited to avoid the possibility of appearance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…1(b)) for FeNi(25). The well defined two peak shape of the MI curves confirms that the effective magnetic anisotropy is a transverse magnetic anisotropy with low dispersion of local easy magnetization axes [2,[8][9].…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…1(b)) for FeNi(25). The well defined two peak shape of the MI curves confirms that the effective magnetic anisotropy is a transverse magnetic anisotropy with low dispersion of local easy magnetization axes [2,[8][9].…”
Section: Resultssupporting
confidence: 54%
“…One can see that for a very wide frequency range asymmetric multilayers with the top layer thicker than 100 nm show a higher magnetoimpedance ratio. In previous studies of FeNi/Cu-based symmetric multilayers with FeNi layers of 100 nm they observed that the system reached the highest MI for the thickness of each magnetic multilayer equal or above the thickness of the central Cu-lead [8][9]. This rule does not work for asymmetric structures.…”
Section: Fig 2 (A) Frequency Dependences Of MI Ratio For Total Impeda...mentioning
confidence: 94%
See 2 more Smart Citations
“…Previous studies [ 5 ] have demonstrated that, for FeNi films, once the thickness reaches 200 nm, an out-of-plane magnetization component appears, ruining the in-plane anisotropy and the magnetic softness required for high GMI values. The insertion of 6-nm thick titanium layers between successive 170-nm thick permalloy layers interrupts the developing of the out-of-plane component of the magnetization, allowing to obtain about one micron-thick films without deteriorating the magnetic softness [ 6 ]. It is also possible to increase the GMI performance even at lower frequencies, creating a sandwich structure by inserting a nonmagnetic layer between two magnetic stacks.…”
Section: Introductionmentioning
confidence: 99%